Post mortem variation in Total Volatile Base Nitrogen and Trimethylamine Nitrogen between Galda (Macrobrachium rosenbergii) and Bagda (Penaeus monodon) - Ali, Mohd Yusuf; Sharif, Md Iqbal; Adhikari, Ripon K; Faruque, Omar (University Journal of Zoology, Rajshahi University, 2010)
Total Volatile Base Nitrgen (TVB-N) and Trimethylamine Nitrogen (TMA-N) of Galda (Macrobrachium rosenbergii) and Bagda (Penaeus monodon) at ambient temperature was compared at Fish Quality Control Laboratory of Fisheries and Marine Resource Technology Discipline, Khulna University, Bangladesh. The TVB-N and TMA-N were determined by using Conway's Micro-diffusion Technique. The nature of biochemical changes was studied up to complete spoilage. The TVB-N contents of Galda and Bagda ranged between 6.65±0.12 mg- N/100g to 8475±0.22 mg-N/100g and 6.72±0.18 mg-N/100g to 91.43±0.49 mg-N/100g. The TMA-N contents of Galda and Bagda ranged between 6.64±0.12 mg-N/100g to 39.38±0.33 mg-N/100g and 6.81±0.17 mg-N/100g to 71.41±0.35 mg-N/100g. A slight higher amount of TVB-N was observed at all stages in Galda as compared to Bagda. TMA-N contents significantly varied between Galda and Bagda (P≤0.05). At all stages of spoilage Bagda showed higher amount of TMA-N. Keywords: Post mortem; TVB-N; TMA-N; Galda and Bagda. DOI: 10.3329/ujzru.v28i0.5278 Univ. j. zool. Rajshahi. Univ. Vol. 28, 2010 pp. 07-10